2009
DOI: 10.1515/znc-2009-7-809
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activities of Endophytic Fungi Isolated from the Endangered, Chinese Endemic Species Dysosma pleiantha

Abstract: Eleven strains of endophytic fungi which habitat in an endangered, Chinese endemic medicinal plant, Dysosma pleiantha (Hance) Woodson, were isolated and tested for their cytotoxic activity using the brine shrimp lethality bioassay. Six isolates were found to exhibit some cytotoxic activity. Extracts of F1273, F1276, and F1280, which were identifi ed as Trichoderma citrinoviride, Chaetomium globosum and Ascomycete sp., in particular, showed most potent activity with LC 50 values of 4.86, 7.71, and 14.88 µg/ml, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(9 reference statements)
1
0
0
1
Order By: Relevance
“…The cytotoxicity assay using the brine shrimps revealed that all extracts were less toxic to brine shrimps compared with podophyllotoxin (LC 50 2.72 μg/mL, Table 3), a well-known cytotoxic lignin. Our findings correlate with other findings on cytotoxicity of fungal extracts (Lu and Wang, 2009). Based on the observed brine shrimp larvae lethality test, it can be speculated that these fungal extracts could possess some anticancer, larvicidal or pesticidal potential.…”
Section: Cytotoxic Activitiessupporting
confidence: 93%
“…The cytotoxicity assay using the brine shrimps revealed that all extracts were less toxic to brine shrimps compared with podophyllotoxin (LC 50 2.72 μg/mL, Table 3), a well-known cytotoxic lignin. Our findings correlate with other findings on cytotoxicity of fungal extracts (Lu and Wang, 2009). Based on the observed brine shrimp larvae lethality test, it can be speculated that these fungal extracts could possess some anticancer, larvicidal or pesticidal potential.…”
Section: Cytotoxic Activitiessupporting
confidence: 93%
“…Microrganismos que residem nas plantas, cada vez mais, estão se tornando objeto dos esforços em pesquisa, visto que os mesmos demonstram capacidade de produzir substâncias com atividades antioxidantes, antibacterianas e tóxicas [1,2] . Uma característica adicional importante é que essas moléculas são altamente seletivas e específicas baseadas nos mecanismos de ação [3] .…”
Section: Introductionunclassified